UJI BEBERAPA DOSIS PUPUK HAYATI BERBAHAN AKTIF Bacillus sp.PADA PERTUMBUHAN DAN HASIL PADI SAWAH (Oryza sativa L.) DENGAN METODE SRI - Ahmad Anhar Syahputra; Murniati '; Fifi Puspita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of research to study determines the effect multiple doses of biofertilizer contain an active Bacillus sp. and obtain the best dose on growth and productivity of paddy (Oryza sativa L). The research was conducted in Pekanbaru Agricultural Quarantine Laboratory and the experimental field of Agriculture faculty, Riau University beginning December 2013 to May 2014. The experiment was designed a completely randomized design (CRD) consisting of 5 treatments and 4 replications. The research treatments are Ph0 (control), Ph1 (15 ml/plant), Ph2 (30 ml/plant), Ph3 (45 ml/plant) and Ph4 (60 ml/plant). The data were analyzed using analysis of variance and followed by Duncan's New Multiple Range Test on level 5%. The result showed that treatments of Biofertilizer contain an active Bacillus sp. has non-significant among plant height, number of total tillers, tiller productive percentage, harvesting, panicle length and number of grains per panicle. But the application of dose 45 ml/plant showed significant on weight of dry grain and weight of 100 grains. Keywords: Bacillus sp. Biofertilizer and SRI Method.